MENEGUHKAN KEMBALI BUDAYA PESANTREN DALAM MERAJUT LOKALITAS, NASIONALITAS, DAN GLOBALITAS - Mukhibat Mukhibat (Karsa: Journal of Social and Islamic Culture, 2015)
Pesantren and its social religious teaching is a complex and challenged issue. This paper analyzed with the historical-critical approach and reflective logic was aimed to claim that pesantren should behave wisely and carefully to confront extremely purification movement and globalization symptom. To purify Islam leads to the failure to understand and identify Islamic power to discuss creatively with local wisdom. Whereas, with the global growth and modern culture, some pesantrens show an ambiguity and unclear direction and the goal in modernizing pesantren. Pesantren has missed its ability to define and place its position amid global reality at the intersection of maintaining the tradition and adopting the new development. For that, with the strong of pesantren cultural tradition, pesantren must be able to make continuity and change to bind local, national, and global values. In other words, the future of pesantren is determined by an education model which relates pesantren cultural values, nationality, and global human issues.Copyright (c) 2015 by KARSA. All right reservedDOI: 10.19105/karsa.v23i2.717